ILMU USHULUDDIN DAN ISSUE STRATEGIS DI ACEH - Rijal, Syamsul (UIN Ar-Raniry, 2014)
Abstract: Memorandum of Understanding (MoU) foreclose the intelectual attention and scientific challenges that are able to provide a positif solution in dynamic changes. Islamic application law on Ã¢â‚¬Âdejure and defactoÃ¢â‚¬Â as well as challenges that actually require the application of thought in law that is more dynamic and solution adaptive responding to the uptodate issues, and in turn there will be the suit to the existance and provide the chance of theology and challenges of dynamic changing of how it should be in the development og theology. The faculty of theology can be a strategic role as a concerstone institution development is surruounded by the reseachers qualified as the agent of change to the human life.